THE EFFECT OF TOURISM ON ECONOMIC GROWTH: EMPIRICAL STUDY IN EASTERN INDONESIA - Purnomo, Sodik Dwi (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.11.NO.08.TAHUN.2022, 2022)
Previous empirical studies on the relationship of the tourism sector to economic growth have shown inconclusive results. Besides, the tourism sector has a low contribution to economic growth. This study aims to analyze the influence of local tourists, foreign tourists, the number of non-productive age residents, education, and health on economic growth in Eastern Indonesia. The research method in this study is using multiple linear regression with a panel data model. The data are annual data of 12 provinces with the period from 2010 to 2019. The results showed that local tourists, foreign tourists, the level of education and health had a significant positive effect on economic growth in Eastern Indonesia. Meanwhile, the non-productive age residents do not affect economic growth in Eastern Indonesia. The implications of this study are 1) the need to develop tourism infrastructure and 2) the need to improve the quality of human resources in the education and health sectors in Eastern Indonesia.